Gen-Z Marketing Strategies: Understanding Consumer Preferences and Building Sustainable Relationships - Salam, Karta Negara; Singkeruang, A. We Tenri Fatimah; Husni, M. Fahrul; Baharuddin, B.; A.R, Dhita Pratiwi (Manunggal Halim Jaya, 2024)
In the contemporary digital landscape, marketing strategies have become increasingly intricate due to the influence of Generation Z, a significant consumer group born between the mid-1990s and the early 2010s. This generation, labeled as